Experiencia de Aprendizaje Mediada de Reuven Feuerstein: una revisión sistemática - dos Santos Lima, Fabio (2023)
The objective of this study is to present a systematic review of literature produced in Brazil on the Mediated Learning Experience (MLE) by teachers in basic education. The review considers studies by Reuven Feuerstein between 2000 and 2020 in Portuguese, Spanish, and English. Four databases, namely VHL, SciELO, Capes, and Pepsic were searched using the following descriptors: Aprendizagem Mediada, Mediação, Mediação Docente, Professor Mediador, Pedagogia e Mediação, Aprendizaje Mediado, Mediación, Mediación Docente, Maestro Mediador, Pedagogía y mediación Feuerstein, Mediated Learning Experience, Mediated Learning, and Modificabilidade. The OR and END operator was used to combine these descriptors. The analysis revealed that there are numerous studies on MLE in special education and teacher training. However, there is a lack of research on MLE with regard to students in basic education in general. These findings lead us to conclude that Feuerstein’s mediated learning is an under-researched area, indicating the need to understand and interpret the importance of this theme for education.